The role of package design typicality on a hand sanitizer purchase. Issue 10 (3rd July 2022) - Frierson, Ami; Hurley, Rupert A.; Kimmel, Robert M.; Griffin, Sarah; Bridges, William; Roth, Ginger; Kessler, Samuel J.
Abstract : This descriptive research uses multiple methods to understand consumers' interactions with hand sanitizer packaging at the point of purchase during the coronavirus pandemic. An analysis of common visual codes within the product category defines a typical hand sanitizer package at the time of the study. Eye‐tracking biometrics systematically describe consumers' attention to hand sanitizer products while shopping. Finally, quantitative and qualitative survey data capture participants' perceived typicality of hand sanitizer packaging, package element preferences and their attitude towards the product. A multiple regression analysis found that visual appeal, brand confidence and packaging have a significant positive relationship to participants' perceived typicality. Packages perceived as typical were best described as transparent with non‐pigmented products and few graphical elements included on the principal display panel (PDP). Form, dispensing method and active ingredient were the most important considerations in hand sanitizer purchases. Participants indicated that brand was not an important factor when shopping for hand sanitizer, but biometrics suggested that it was more important than most other text. Findings contribute to the growing research around package design typicality with a novel product category and offer a baseline understanding of expectations for hand sanitizer packaging. Attention towards 11 hand sanitizer packaging stimuli and survey responses of 61 human subjects located in the southeast United States during the coronavirus pandemic were collected and analysed. Further research is needed to understand consumer interaction with hand sanitizer packaging outside this context. Abstract : This descriptive research uses multiple methods to understand consumers' interactions with hand sanitizer packaging at the point of purchase during the coronavirus pandemic. A multiple regression analysis found that visual appeal, brand confidence and packaging have a significant positive relationship to participants' perceived typicality of a package design. Results suggest that package design typicality does influence consumer attention, but visual appeal and brand confidence may have a larger impact on a hand sanitizer purchase than perceived typicality.